Marine pollution contingency planning : state practice in Asia-Pacific states - Telesetsky, Anastasia (Maritime cooperation in East Asia, 2017)
There is an ever-present threat of catastrophic marine pollution incidents, as illustrated by recent disasters such as the Deepwater Horizon oil spill in the Gulf of Mexico. Even small-scale accidental pollution discharges can have long-term consequences for marine and coastal resources. The UN Convention on the Law of Sea obliges all States to cooperate to prevent accidents and to minimize environmental damage during emergencies by jointly developing and implementing marine pollution contingency plans. The Asia-Pacific is one of the world's busiest shipping regions, some of its mega-ports experience high rates of vessel congestion, and there are increasing numbers of offshore installations. Marine pollution prevention planning is thus vital for the region. 'Marine Pollution Contingency Planning: State Practice in Asia-Pacific States' outlines and examines marine pollution contingency planning in Australia, Canada, China, Japan, Korea, Malaysia, Mexico, Philippines, Singapore, and the United States.